(untitled) (Al-Farooq Journal of Sciences, 2026)
This research aims to study tourism culture and its impact on the development of the tourism sector in Libya, focusing on the role of the Ministry of Tourism in spreading this awareness and identifying the most appropriate methods for Libyan society. The researcher used the descriptive-analytical approach to diagnose the current reality, relying on a questionnaire as a primary tool for data collection from a random sample of employees at the Ministry of Tourism and Handicrafts. The research found that the lack of tourism cultural awareness among individuals is the fundamental obstacle preventing the effective investment of natural resources and historical monuments. The results also showed the limited role of the Ministry of Tourism in awareness initiatives and the absence of community interaction in tourism activities. Furthermore, the study revealed the existence of social and cultural barriers, such as fear of tourism’s impact on local values and customs, reservations about establishing tourism facilities, and a severe shortage of specialized tourism education and training programs in educational institutions. The research recommended the necessity of enhancing tourism awareness programs through media campaigns and workshops targeting all age groups. It also emphasized the importance of integrating tourism culture into school and university curricula to prepare a generation capable of civilized interaction with visitors. The study called for encouraging community participation in local festivals and exhibitions, and leveraging social media as a strategic tool to promote domestic tourism. Finally, the research suggested establishing specialized training centers and preparing a national guide for tourism culture that defines desired behaviors toward tourism attractions.